Corse de Leon; or, The Brigand: A Romance. Volume 1 (of 2) - James, G. P. R. (George Payne Rainsford), 1801?-1860 (Salt Lake City, UT : Project Gutenberg, 2011)
"Corse de Leon; or, The Brigand: A Romance. Volume 1 (of 2)" by G. P. R. James is a historical novel written in the early 19th century. The story revolves around Bernard de Rohan, a young nobleman and soldier who experiences a mix of joy and sorrow as he navigates life during the turbulent period of the 16th century, amidst themes of chivalry, romance, and adventure. Set in the picturesque landscape of Savoy and featuring a cast of intriguing characters, including the enigmatic brigand Corse de Leon, the narrative promises an exploration of love, honor, and the moral complexities of its time. The opening of the novel sets a contemplative tone, reflecting on the fleeting nature of happiness and the inevitability of sorrow. It introduces the main character, Bernard de Rohan, who, after a bright day of riding through the lush valleys and majestic mountains, begins to feel an inexplicable gloom overshadowing his spirit. Joined by a jovial priest and his servants, he embarks on a quest for refuge as a storm gathers above. The ominous atmosphere hints at forthcoming trials. Soon, Bernard encounters a scene of abduction involving bandits, leading him to join forces with Corse de Leon to rescue the captives, setting the stage for a tale of intrigue and valor intertwined with personal stakes and romantic pursuits. (This is an automatically generated summary.)
Release date is 2011-05-06
E-text prepared by Barbara Tozier, Bill Tozier, Mary Meehan, and the Online Distributed Proofreading Team
Keywords: France -- History -- Henry II, 1547-1559 -- Fiction